Seleno‐methionine decreases biohydrogenation of C18 unsaturated fatty acids in ovine ruminal fluid incubated in vitro with α‐linolenic acid. Issue 6 (22nd January 2015) - Czauderna, Marian; Rozbicka‐Wieczorek, Agnieszka J.; Więsyk, Edyta; Krajewska‐Bienias, Katarzyna A.
<x xml:space="preserve">Abstract</x> The influence of seleno‐methionine (Se‐Met) added to an ovine ruminal fluid containing α‐linolenic acid (α‐LNA) on the profile of fatty acids (FA) was investigated. The fluid was incubated in vitro at 39°C under CO2 either alone (the control ruminal fluid; RF) or with α‐LNA (1.67 mg/mL) or with a combination of α‐LNA with either a low (1.25 µg/mL) or high (4.16 µg/mL) concentration of Se as Se‐Met. Tubes with fluids were removed after 0, 6, 12, 18 or 24 h of incubation. α‐LNA in the fluids with/without Se‐Met stimulated the accumulation of C14:0 and C16:0 compared with the RF. The fluids containing Se‐Met reduced the concentration of C18:0 compared with the RF. α‐LNA in the fluids with/without Se‐Met increased concentrations of cis9C14:1, cis9C18:1 and trans11C18:1 compared with the RF and the fluids with Se‐Met. The fluids with α‐LNA and Se‐Met increased the accumulation of trans9trans11cis15C18:3 compared with the fluids with α‐LNA. The fluids with α‐LNA and Se‐Met decreased the biohydrogenation to C18:0 compared with the RF. Se‐Met in the fluids elevated the concentration of trans11C18:1 and lowered the capacity of the biohydrogenation to C18:0 in the fluids incubated for 24 h. Added Se‐Met affected the FA profile in incubated fluids. Practical applications Selenium and polyunsaturated fatty acids n‐3 (PUFAn‐3) are very important for human health and nutrition. Recent studies documented that a higher content of mono‐conjugated isomers of α‐linolenic acid (α‐LNA) in diets reduced the abundance of PUFAn‐3 in the brain, liver and heart of experimental animals. Due to the increasing world population, overfishing of the seas and usually low concentrations of PUFAn‐3 and essential trace elements (like selenium) in animal products, there is a demand for better methods of feeding livestock. Considering the above, it was desirable to study the extent to which dietary seleno‐compounds (like seleno‐methionine) may contribute to concentrations of mono‐conjugated α‐LNA (C‐α‐LNA) isomers, as C‐α‐LNA isomers may perturb the PUFA balance (or imbalance) in tissues of animals and humans. Moreover, further studies are needed to determine if dietary seleno‐compounds, α‐LNA and C‐α‐LNA isomers also induce changes in concentrations of fatty acids, especially PUFAn‐3, in tissues of lambs. <inline-graphic xlink:href="ark:/27927/pgjr0rqx9d" content-type="ejlt201400476-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Seleno‐methionine has an influence on the concentrations of fatty acids, especially unsaturated fatty acids, in in vitro incubated ovine ruminal fluid, irrespective of the presence of α‐linolenic acid. Seleno‐methionine added to the incubated fluids affects the capacity of the bacterial isomerases and modified activities of ruminal bacteria. The simultaneous addition of α‐linolenic acid and Se‐Met to the ruminal fluids decreased the yield of final biohydrogenation to C18:0 in comparison with the in vitro incubated control fluids.